Overview of the CDC Cervical Cancer (Cx3) Study: An Educational Intervention of HPV Testing for Cervical Cancer Screening - Benard, Vicki B. (J Womens Health (Larchmt), 2013)
BACKGROUND: The recommended screening interval when using the Papanicolaou (Pap) and human papillomavirus (HPV) test (co-testing) is 5 years. However because providers are reluctant to extend the screening interval, we launched a study to identify barriers to appropriate use of the co-test and to implement an educational intervention to promote evidence-based screening practices. This article provides an overview of the study including the multi-component intervention and participant demographics. METHODS: The study was conducted in 15 clinics associated with 6 Federally Qualified Health Centers (FQHCs) in Illinois. Each clinic received HPV tests to administer with routine Pap tests among enrolled patients (n = 2,246) and was assigned to a study arm: intervention arm (n = 7) received a multi-component educational intervention (small media, academic detailing, and website) for providers and printed educational materials for patients, and control arm (n = 8) received printed copies of general guidelines. Clinic coordinators (n = 15), providers (n = 98), and patients (n = 984) completed baseline surveys to assess screening practices. RESULTS: Providers reported an average age of 41.3 years and were predominately female, non-Hispanic, and white. Patients reported an average age of 45.0 years and nearly two-thirds were Hispanic or black. Of the 2,246 patients, 89% had a normal co-test. Lessons learned from the study included the importance of buy-in at a high level in the organization, a champion provider, and a clinical coordinator devoted to the study. CONCLUSION: Materials from this study can be adapted to educate providers and patients on appropriate use of the co-test and encourage extended screening intervals as a safe and effective practice.